Pola Pertumbuhan dan Faktor Kondisi Ikan Duri (Hexanematichthys sagor) yang Tertangkap di Perairan Sungai Maro Kabupaten Merauke Propinsi Papua Selatan - Saleky, Dandi; Jubaidah, Siti; Pangaribuan, Rosa D.; Situmorang, Ferdinand C.; Welliken K., Marius A. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the growth pattern of barbfish, the condition factors of barbfish, and the water parameters (temperature, brightness, pH, and salinity) in the Maro River waters. This research was conducted in April – June 2024 using the Purposive sampling method. The results of the study showed  (1) The growth pattern of male and female barbfish at each station shows a positive allometric growth pattern, which means that the increase in fish weight is faster than the increase in fish length. (2) The highest condition factor (FK) value was in the female barbfish caught at station 2 with an average value of 1.0074, the next highest (FK) value was in the male barbfish caught at station 2 with an average value of 1.0013 and the lowest (FK) value was in the male barbfish caught at station 1 with an average value of 0.9885. (3) The results of water quality measurements in the Maro River show that the temperature ranges from 27 – 30oC, clarity 30 – 35 cm, pH ranges from 7.2 – 7.5, and salinity ranges from 25 o\oo – 29 o\oo. Overall, the results show that it still supports the existence of marine biota and has not experienced pollution with a stable category and by the quality standards set by Government Regulation Number 22 of 2021 on Implementation of Environmental Protection and Management.